Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.2355/isijinternational.51.958
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Ultrafine Grained Dual Phase Steels through Rapid Heating

Abstract: In this study, ultrafine grained dual phase structures have been developed in a plain low carbon steel, 0.17C and 0.74Mn (wt pct). The approach is based on rapid heating of a very fine ferrite-carbide aggregate into the intercritical annealing region followed by water quenching. This rapid heat treatment results in an ultrafine grained dual phase steel with improved properties. The effect of thermomechanical processing parameters such as heating rate and intercritical annealing time on the microstructure and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(50 citation statements)
references
References 26 publications
3
43
0
Order By: Relevance
“…Increasing the holding time increases the austenite volume fraction, which then will transform to martensite upon quenching in the water. Therefore, VM increased with increasing intercritical annealing time, as reported by Qu et al 15) and Azizi-Alizamini et al 12) As shown in Fig. 3(b), microstructural feature of the cold-rolled duplex structure is consisted of high density of ferrite/martensite interfaces which can be nucleation sites for austenite formation (Fig.…”
Section: Microstructuressupporting
confidence: 65%
See 3 more Smart Citations
“…Increasing the holding time increases the austenite volume fraction, which then will transform to martensite upon quenching in the water. Therefore, VM increased with increasing intercritical annealing time, as reported by Qu et al 15) and Azizi-Alizamini et al 12) As shown in Fig. 3(b), microstructural feature of the cold-rolled duplex structure is consisted of high density of ferrite/martensite interfaces which can be nucleation sites for austenite formation (Fig.…”
Section: Microstructuressupporting
confidence: 65%
“…Azizi-Alizamini et al 12) also reported that the volume fraction of coarse ferrite grains increased with increasing intercritical annealing time. Figure 7 shows the hardness variation of both 50 and 80% cold-rolled samples with increasing intercritical annealing time.…”
Section: Microstructuresmentioning
confidence: 92%
See 2 more Smart Citations
“…The exact nature of the interaction between ferrite recrystallization and austenite formation in steel has been studied by several authors . The present authors consider that both processes are rather independent of each other due to the different nature of the driving forces involved.…”
Section: Discussionmentioning
confidence: 91%